Predicting Photovoltaic Electrical Power Generation Using Computational Method - Shamsuddin, Siti Diyanah; Nor, Ahmad Fateh Mohamad (Journal of Quranic Sciences and Research, 2022)
One of the most popular kinds of renewable energy in the generation of electric power is the photovoltaic (PV) system. One of the disadvantages of the PV system however is the incompatibility of the performance of PV panels because of the changing climate. Therefore, the optimum power output of the PV system is important to predict. This study will cover the implementation of PV system behind the Faculty Electrical and Electronic Engineering Block QA Building, University Tun Hussein Onn Malaysia. Then, the PV power output is predicted with manual calculation. Temperature and solar irradiance are the important input parameters that need to be taken into the calculation. The result shows that February and March have the highest total power output which 7155203.97 kWh and 7395327.66 kWh than any other month in year 2020.